Peran Himpaudi Dalam Pengembangan Pendidik Pendidikan Anak Usia Dini (Paud) Di Kota Bandar Lampung - Nopaliasari Nopaliasari (El-Idare, 2022)
The purpose of this paper is to obtain data and information about the role of the Association of Indonesian Early Childhood Educators and Education Personnel (HIMPAUDI) in the implementation of PAUD, particularly in terms of: 1) To find out the role of HIMPAUDI in socializing the importance of S1 Education qualifications to PAUD educators. 2) To find out how the role of HIMPAUDI in the Guidance and Development of PAUD educators through tiered education and training. 3) To find out how HIMPAUDI's role is in accommodating, fighting for and realizing the aspirations of PAUD educators to get welfare, 4) To find out how HIMPAUDI's role is in facilitating training for PAUD educators through the delivery of national level training. The findings of the analysis of this paper are: 1) the role of HIMPAUDI in socializing the importance of S1 Education qualifications to PAUD educators through various ways, namely providing input to PAUD educators to take part in the PAUD S1 lecture program at universities in the city of Bandar Lampung; 2) in the Guidance and Development of PAUD educators through tiered training, it is expected that PAUD educators will be willing to participate in Tiered Education independently; 3) HIMPAUDI has fought for educators to obtain incentives, both received from the Government and businesses developed by HIMPAUDI; and 4) HIMPAUDI's role in facilitating training for PAUD educators through the delivery of national level training through regional and city administrators in accordance with central regulations. The method used is observation, interviews and documentation.